The Evaluation of The Principal’s Performance in Improving Teacher Performance - Jhon S Pasaribu; Bambang Ismanto; Wasitohadi Wasitohadi (CV. Publikasi Indonesia, 2024)
This research aims to determine the performance of school principals and how it influences teacher performance. This research is evaluation research with a discrepancy model and a research approach using descriptive qualitative. The subject of this research is SD Negeri 02 Kumpulrejo Salatiga. Data collection techniques use qualitative data collection techniques through interviews, observation, and documentation. Data triangulation uses technical triangulation and source triangulation. Technical triangulation was carried out through interviews, documentation studies, and observations. Source triangulation was carried out by matching the results of the principal's interview with the results of interviews with teachers, supervisors, and school committees by providing the same question instrument. The data analysis technique consists of three activity streams, namely data reduction, data presentation, and conclusion. The results of the research show that from each stage in the discrepancy evaluation model, namely the design, installation, process, product, and cost-benefit stages, it is stated that the principal's managerial performance has met the standards of adequacy, suitability, and fairness. So it can be concluded that the principal has been able to carry out his managerial competencies well.